Investigation of Screw Compressors for Low Pressure Ratio Applications. Issue 1 (September 2021) - Lu, Y; Kovacevic, A; Read, M; Buckney, D; Endo, Y
Abstract: Screw compressors have been widely investigated for many applications including air and process gas compression, and refrigeration systems. There is however a surprising lack of literature for low pressure ratio application of these machines, defined here as application requiring volume ratios in the range of 1-1.5. The aim of this paper is to characterise the loss mechanisms for oil injected screw compressors with low volume index (defined as the ratio of maximum to minimum volumes during the internal compression process), V i . This knowledge will be applied in the future to identify appropriate optimisation of rotor profiles and porting geometry for a range of low-pressure ratio applications. The current study involves the use of chamber models to investigate the influence of wrap angles and porting. This initial analysis will be developed in future work to allow a detailed parametric study of the factors that limit the performance of low V i oil-injected screw compressors.